Penerapan Data Mining untuk Klasterisasi Data Anggaran Pendapatan dan Belanja Daerah Menggunakan Algoritma K-Means - Widianto; M. Rifqy Zakaria; Irvan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
To continue the development relay and fulfill the transition period until the simultaneous elections are held, it is necessary to prepare a Regional Development Plan (RPD) for regional heads whose terms of office end in 2022. The K-Means algorithm approach can be applied in analyzing the level of potential regional income and expenditure based on regional income and expenditure clusters that have results in the K-Means algorithm testing process, two clusters cluster 1 (C0) is a category of high spending potential consisting of and cluster 2 (C1) and is a low spending potential. The applied K-Means algorithm model has results that show a new insight, namely the grouping of regional income and expenditure budget data for the Tolikara Regency BPKAD based on 2 clusters has cluster results of 47 and 3. In analyzing the level of potential regional income and expenditure, the results of the test have centroid results 1 192973008, 16700000 and centroid results 2 7000000 and 225000000.